Archive as Laboratory: Engaging STEM Students & STEM Collections. Issue 2 (4th May 2019) - Grimm, Tracy B.; Vostral, Sharra
ABSTRACT: As STEM students come to populate undergraduate courses in the liberal arts to fulfill university distribution requirements, they outnumber their humanities counterparts. A history professor and archivist working at a university that predominantly produces STEM majors have partnered to teach these students by utilizing the special collections related to engineering, innovation, and discovery in classroom work and assignments. This Critical Participation article presents the model of the 'archive as laboratory' to facilitate critical inquiry, introduce archival literacy to scientists and engineers, and expand students' concept of information sources. Students gain an understanding that research questions can be addressed through multiple kinds of evidence that the archives is uniquely situated to provide. The immersive learning experience is enhanced by coursework that incorporates foundational theories and approaches from Science & Technology Studies. The lab model engages the archive as a hands-on workspace and a place where students can practice research skills. Engaging the archive as a laboratory fosters inquiry and critical thinking, and connects histories of innovation, problem identification, and design practice to students' own majors and their future careers. It is relevant when a problem requires original solutions not found in existing manuals, textbooks, or online platforms.